EVALUACIÓN PRESUPUESTARIA AL GOBIERNO AUTÓNOMO DESCENTRALIZADO DEL CANTÓN CENTINELA DEL CÓNDOR PERIODO 2010-2011 - SOTO TORRES, GRACIELA ELIZABETH (2016)
The Self-Government Decentralization of Canton Centinela del Condor is an entity that provides services to the community in a timely and flexible manner moments so requires, so it has earned the reputation as a state entity that manages public funds for compliance their institutional mission and vision. The work done can comply with the proposed objectives and referring to perform an analysis of variations suffering budgetary allocations in these two years, and determine the causes of these variations by applying budgetary indices to help to measure the degree of efficiency and effectiveness in the use of resources allocated to that entity. The methodology developed for practical begins with the collection of reliable and objective information from the authorities of the institution, to proceed to implement a study of revenues and expenses incurred by the Autonomous Decentralized Government, through the cedulas budget legalized, and confirm their relevance and efficiency when using or allocate funds to different areas that comprise the entity. Then the variation of the budget items of income and expense in order to know what are the causes that led to these changes and whether they are 5 favorable on for the interest of the entity under consideration is determined. Following the implementation of budget consists indexes using comparative tables of budget execution in 2010-2011, which allowed to present the variations between executed and budgeted revenues and expenditures, by applying statistical tables determined increases or decreases from one period to another. The main conclusion of the research work is that the entity has not earned efficiently income, limiting their actions and service to the geographical environment in which performs its functions. Furthermore policies should take into account in formulating the budget in order that these serve as a guide when developing it intends finally the conclusions and recommendations to the most relevant aspects that have been discovered are left to conclude raised this work, in order to provide a significant contribution which serve to make internal corrective measures and improve budget management in the coming periods.